Peran Kantor Urusan Agama Dalam Mengurangi Pernikahan Sirri di Kecamatan Bojong Gede - Ummu Zahratun Nabila; Yono Yono; Suyud Arief (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Sirri marriages among Indonesian Muslims have been widely known, especially after the enactment of Law Number 1 of 1974 concerning Marriage and the ratification of Government Regulation Number 9 of 1975 concerning Implementing Regulations of Law Number 1 of 1974. Some Muslims in Indonesia believe that Marriage without going through the registration of the KUA is considered valid according to Islamic law if it has fulfilled the pillars and conditions, even though the marriage is not officially registered. But in reality, underhand marriage is a problematic marriage model and tends to prioritize subjective interests. This study aims to find out how the role of KUA in reducing sirri marriages in the district of Bojong Gede. The data used in this study are, first, primary data, namely data obtained by conducting interviews with the perpetrators of unregistered marriages, as well as interviews with the Head of KUA Bojong Gede District. Second, secondary data is data obtained from various literatures such as scientific articles, books, and journals related to research. The results showed that the role of KUA in reducing unregistered marriages in the Bojong Gede sub-district, Bogor district, included: Conducting socialization at every weekly meeting about the importance of recording marriages and the negative impact of unregistered marriages, holding outreach during official meetings involving elements of musfika about understanding the importance of marriage. the marriage was officially registered. KUA Bojong Gede held an approach to the community in the form of seminars as well as studies, the approach was carried out through the taklim assembly in the community with an explanation that there were more negative impacts obtained from unregistered marriages than positive impacts. Keywords: Role, KUA, Sirri Marriage,